2013
DOI: 10.2166/wst.2013.731
|View full text |Cite
|
Sign up to set email alerts
|

Application of artificial neural network for modeling of phenol mineralization by photo-Fenton process using a multi-lamp reactor

Abstract: An artificial neural network (ANN) was implemented for modeling phenol mineralization in aqueous solution using the photo-Fenton process. The experiments were conducted in a photochemical multi-lamp reactor equipped with twelve fluorescent black light lamps (40 W each) irradiating UV light. A three-layer neural network was optimized in order to model the behavior of the process. The concentrations of ferrous ions and hydrogen peroxide, and the reaction time were introduced as inputs of the network and the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…although the available information is presented in different forms and usually the resulting accuracies are not referred to the accuracy of the raw information, common CC results are in the range [0.84 -0.95] (Grbic et al, 2013;Jin et al, 2015), and values of RMSE of 3.35 (Mota et al, 2014) and average relative errors of 15% (Duran et al, 2006) are reported.…”
Section: Accuracy Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…although the available information is presented in different forms and usually the resulting accuracies are not referred to the accuracy of the raw information, common CC results are in the range [0.84 -0.95] (Grbic et al, 2013;Jin et al, 2015), and values of RMSE of 3.35 (Mota et al, 2014) and average relative errors of 15% (Duran et al, 2006) are reported.…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…A different class of data-based modeling studies has been focused on the prediction of the contaminant degradation dynamics during the treatment time (Göb et al, 1999;Salari et al, 2005;Elmolla et al, 2010;Ayodele et al, 2012;Mota et al, 2014;Mustafa et al, 2014;Gazi et al, 2017;Sebti et al, 2017). To do so, the degradation evolution is assumed to be a function of the initial experiment parameters (e.g.…”
Section: Application To a Photo-fenton Batch Processmentioning
confidence: 99%
“…As an alternative to physical models, an ANN is a valuable forecast tool in environmental sciences [24]. The ANN can be used effectively due to its learning capabilities and its low computational costs [25]. Because of their reliable, robust, and salient characteristics in capturing the non-linear relationships between variables (multi-input/output) in multivariate systems, numerous applications of ANN-based models have been successfully utilized in the field of environmental engineering in the past decade [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are more difficult to remove from water by using conventional treatment techniques. Therefore, it is necessary to apply more advanced techniques that allow the degradation of these compounds (Yavuz and Koparal, 2006;Saien and Nejati, 2007;Mota et al, 2014). One of the alternatives is advanced oxididation processes (AOPs).…”
Section: Introductionmentioning
confidence: 99%